« La Loi canadienne sur les droits de la personne » : une Charte méconnue - Lemieux, Denis; Lachapelle, Andrée; Lévesque, Suzanne (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1982)
While the Constitutional Charter of Rights and the Canadian Bill of Rights have benefited to some degree from the debates and criticisms surrounding their adoption and application, few jurists are aware of the Canadian Human Rights Act. This statute pursues at the federal level the same goals as those set forth in provincial human rights legislation such as the Charte des droits et libertés de la personne. It applies to more than ten per cent of the Quebec labour force and, therefore, is not without influence in the implementation of human rights policies and the redress of grievances. The purpose of this paper is to compare the Canadian Human Rights Act with other existing charters. In a first part, we will present the nature and scope of the Act, in a comparative perspective. The second part of the paper will deal with the implementation of the Act by the Canadian Human Rights Commission and Tribunals, also in a comparative perspective.